BANJIR BANDANG DI DAS BATANG KURANJI KEC. KURANJI KOTAPADANG DENGAN SISTEM INFORMASI GEOGRAFIS (SIG) - Pelly, Dandi Arianto; Saputra, Roni Haryadi; Dewi, Rosita; Rahman, Auliya; Nasrul, M.Rozi (Program Kreativitas Mahasiswa - Penelitian, 2013)
The research aims to map hazard flash flood sand Inundation mapping the spatial distribution(affected by) flash floods and analyze the factors causing flash floods in Batang Kuranji Watershed Sub- District Kuranji Padang. The method used is a 3D analysis of data raster DEM, topographic slope, Slope, flood elevation data, and river network data, for mapping the spatial distribution affected by the flash floods using survey methods to map land units as mapping unit. GPS tracking is then performedin the field to produce spatial distribution maps Inundation (affected by) flash floods and flash floods causing factor data were analyzed using the scoring methodo fland characteristics as determinants offlash flood hazard. From this research, the proportion of flood hazard zones with high hazard category with abroad zone of 1320 ha, or 6,15% of the region Batang Kuranji. Medium hazard zones are an area of 1243 ha or 5,7% of the region Batang Kuranji, and low hazard zones in the study region has an area of 18 885ha with aproportion of 88,15% of the total land area ofresearch Batang Kuranji and spatial distribution of the inundations flash floods in the area along Kuranji watershed in Koto Tangah subdistrict, Kuranji subdistrict, Nanggalo subdistrict, North Padang subdistrict, and Pauh subdistrict. Causing factor flash flood in the research area are mass movement that of caused landform, slope, slopeform, long of slope, and geomorphology process.Â Keywords : flash floods, spatial distribution, inundation.